CHARACTERISTIC OF EMOTIONAL STATES OF THE ADULTS IN A SITUATION OF PROLONGED ABSENCE OF A ROMANTIC RELATIONSHIP - Opekina, Т.P. (Modern Psychology, 2019)
The article presents the results of a study devoted to qualitative and quantitative study of emotional States of men and women at the stage of early adulthood in the situation of long-term absence of romantic relationships. The connections of alarming, subdepressive States, experiences of loneliness of such subjects with their personal characteristics, meanings of creation of romantic relations in the long term are described. The specificity of the image of future romantic relationships and the image of a romantic partner is considered as a factor determining the subject's own activity in creating romantic relationships. Characterological features of the subjects most strongly experiencing depression, rejection, loneliness are described. On the basis of qualitative research (interview) the meanings of romantic relationships between adult men and women with different characterological characteristics, with different subjective perception of the long absence of romantic relationships in the dichotomy "loneliness/freedom", with different degrees of need for intimacy are analyzed.
Keywords: romance, emotional state, sense relations, loneliness, subdepressive, anxiety.